Chloromethane formation and degradation in the fern phyllosphere - Jäger, Nicole; Röhling, Amelie Ninja; Koch, Fabien; Greule, Markus; Keppler, Frank (The science of the total environment, 2018)
Chloromethane (CH3Cl) is the most abundant halogenated trace gas in the atmosphere. It plays an important role in natural stratospheric ozone destruction. Current estimates of the global CH3Cl budget are approximate. The strength of the CH3Cl global sink by microbial degradation in soils and plants is under discussion. Some plants, particularly ferns, have been identified as substantial emitters of CH3Cl. Their ability to degrade CH3Cl remains uncertain. In this study, we investigated the potential of leaves from 3 abundant ferns (Osmunda regalis, Cyathea cooperi, Dryopteris filix-mas) to produce and degrade CH3Cl by measuring their production and consumption rates and their stable carbon and hydrogen isotope signatures. Investigated ferns are able to degrade CH3Cl at rates from 2.1 to 17 and 0.3 to 0.9μggdw−1day−1 for C. cooperi and D. filix-mas respectively, depending on CH3Cl supplementation and temperature. The stable carbon isotope enrichment factor of remaining CH3Cl was −39±13‰, whereas negligible isotope fractionation was observed for hydrogen (−8±19‰). In contrast, O. regalis did not consume CH3Cl, but produced it at rates ranging from 0.6 to 128μggdw−1day−1, with stable isotope values of −97±8‰ for carbon and −202±10‰ for hydrogen, respectively. Even though the 3 ferns showed clearly different formation and consumption patterns, their leaf-associated bacterial diversity was not notably different. Moreover, we did not detect genes associated with the only known chloromethane utilization pathway “cmu” in the microbial phyllosphere of the investigated ferns. Our study suggests that still unknown CH3Cl biodegradation processes on plants play an important role in global cycling of atmospheric CH3Cl.